2016
DOI: 10.1111/cge.12775
|View full text |Cite
|
Sign up to set email alerts
|

Specific mosaic KRAS mutations affecting codon 146 cause oculoectodermal syndrome and encephalocraniocutaneous lipomatosis

Abstract: Oculoectodermal syndrome (OES) and encephalocraniocutaneous lipomatosis (ECCL) are rare disorders that share many common features, such as epibulbar dermoids, aplasia cutis congenita, pigmentary changes following Blaschko lines, bony tumor-like lesions, and others. About 20 cases with OES and more than 50 patients with ECCL have been reported. Both diseases were proposed to represent mosaic disorders, but only very recently whole-genome sequencing has led to the identification of somatic KRAS mutations, p.Leu1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 49 publications
1
57
0
Order By: Relevance
“…The OES, ECCL, and SFMS syndromes are a group of oculocutaneous developmental mosaic RASopathies which exhibit common anomalies including focal scalp lesions, linear cutaneous hyperpigmentation, arachnoid cyst, and cardiac defects (Ardinger, Horii, & Begleiter, ; Ernst, Quinn, & Alawi, ; Moog, ). At the molecular level, these entities are caused by somatic mosaicism for mutations in genes encoding components of the RAS signaling pathway (Bennett et al, ; Boppudi et al, ; Groesser et al, ; Peacock et al, ). OES is a very rare disease characterized for a consistent combination of scalp lesions and epibulbar dermoids (Toriello, Lacassie, Droste, & Higgins, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The OES, ECCL, and SFMS syndromes are a group of oculocutaneous developmental mosaic RASopathies which exhibit common anomalies including focal scalp lesions, linear cutaneous hyperpigmentation, arachnoid cyst, and cardiac defects (Ardinger, Horii, & Begleiter, ; Ernst, Quinn, & Alawi, ; Moog, ). At the molecular level, these entities are caused by somatic mosaicism for mutations in genes encoding components of the RAS signaling pathway (Bennett et al, ; Boppudi et al, ; Groesser et al, ; Peacock et al, ). OES is a very rare disease characterized for a consistent combination of scalp lesions and epibulbar dermoids (Toriello, Lacassie, Droste, & Higgins, ).…”
Section: Discussionmentioning
confidence: 99%
“…Three additional syndromes with overlapping clinical findings in eye, heart, skin, and hair have been recently shown to result from somatic mosaicism for mutations in the genes involved in the Ras pathway, including KRAS [OMIM *190070], HRAS [OMIM *190020], NRAS [OMIM *164790], and FGFR1 [OMIM *136350]. These entities are the oculoectodermal (OES, OMIM %600268) and Schimmelpenning‐Feuerstein‐Mims syndromes (SFMS, OMIM #163200), as well as encephalocraniocutaneous lipomatosis (ECCL, OMIM #613001), oculocutaneous disorders exhibiting pleiotropic anomalies that include scalp lesions, epilepsy, epibulbar dermoids, cloudy cornea, eyelid coloboma, coarctation of the aorta, and skin pigmentation abnormalities (Boppudi et al, ; Groesser et al, ; Kuroda et al, ; Peacock et al, ). Somatic mutations causing oculocutaneous mosaic RASopathies are recurrent and have been identified at KRAS codons 13, 19, and 146 in OES patients (4 subjects reported to date) (Boppudi et al, ; Peacock et al, ), KRAS codon 146 and FGFR1 codons 546 and 656 in ECCL (six reported patients) (Bennett et al, ; Boppudi et al, ), and HRAS codon 13 (2 patients), KRAS codon 12 (3 subjects), and NRAS codon 61 (1 subject) in individuals with a SFMS diagnosis (Groesser et al, ; Igawa et al, ; Kuroda et al, ; Lihua, Feng, Shanshan, Jialu, & Kewen, ; Sun et al, ; Wang, Qian, Zhang, & Zhou, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3]. NS features include abnormal growth (proportionate short stature and relative or absolute macrocephaly), congenital heart defects (most commonly pulmonary stenosis or hypertrophic cardiomyopathy), dysmorphism (hypertelorism with downslanting palpebral fissures; ocular ptosis; low-set, posteriorly rotated ears; broad neck with low hairline; and thorax deformity), and abnormal skin and adnexa.…”
Section: The Rasopathiesmentioning
confidence: 99%
“…Additional features may include learning difficulties, ocular anomalies, feeding problems in infancy, cryptorchidism, disorders of pubertal timing, lymphatic anomalies, bleeding diathesis, and increased cancer risk. The group of RASopathies are described in detail below (1)(2)(3). Among these are neurofibromatosis type 1 (NF1); cancer surveillance in persons with NF1 is discussed in the CCR Pediatric Oncology Series article by Evans and colleagues (4).…”
Section: The Rasopathiesmentioning
confidence: 99%